Dilema Demokrasi Liberal: Hambatan Normatif, Institusional dan Praktikal dalam Pemberlakuan Kuota Perempuan di Indonesia - Nur Azizah (Universitas Muhammadiyah Yogyakarta, 2014)
Political reform in 1998 Indonesia brought an inclusive participation to all people. One of its significant outcomes was the establishment of women quota that tried to accommodate women’s aspirations in Indonesian democratic system, particularly in the parliament. This policy had been legalized in the constitution article 65 UU 12 2003 about General Election of the House of Representative which then finalized in 2008. However, this quota mechanism has many barriers in its implementation such as from Mahkamah Konstitusi that decided to change the instrument for elected candidate which based not on the consecutive number, so the quota system was complicated to put into practice. This article tries to explain why the performance of women quota was ineffective. To address the problems, analysis of this article based on feminist perspective with critical discourse of analysis (CDA). The study will be conducted on three levels namely normative level, institutional level, and practical level.